Establishment Pattern of Group of Action Research Package Recivers through Community Participation - Clara M Koeskarto; Nino Y Sadiyyah; Ali Khomsan; Emmy Karsin; . Retnaningsih (Media Gizi dan Keluarga, 2000)
The objective of the research is to establish family to improve family wellfare, particulary in food consumption (quantity and quality/diversity) through community participation. An action research was conducted in Bogor district, samples were Keluarga Prasejahtera (PS) and Keluarga Sejahtera I (KSI) who had children under five years old. Data collected were: Socio economic, food consumption, nutrition knowledge, food habit, nutritional status and family respond to program sustainability. The results of this study showed that energy and protein consumption were worse than that of one year ago which is caused by economic cricis and dryness condition. However food diversity and nutritional status were better than that of one year ago. There were a positive correlation among energy and protein consumption, food consumption diversity and nutritional status with the duration of participation. There was olso an economic impact due to animal package intervention. Near 100% of the families explained they would contuinue to participatte in the program, and they felt the advantages of the program existence.